Plasmodium chabaudi AS Infection Induces CD4+ Th1 Cells and Foxp3+T-bet+ Regulatory T Cells That Express CXCR3 and Migrate to CXCR3 Ligands - Berretta, Floriana; Piccirillo, Ciriaco A.; Stevenson, Mary M. (Frontiers in Immunology, 2019)
Control and elimination of blood-stage P. chabaudi AS infection requires CD4+ Th1 cells that secrete IFN- and T follicular help (Tfh) cells together with B cell production of antibody. Foxp3+ regulatory T cells (Tregs) are also crucial to protect the host from immunopathology and severe disease, but these cells can suppress protective immune responses to malaria. The chemokine receptor CXCR3 expressed by activated T cells is important for trafficking of CD4+ Th1 cells to sites of inflammation and infection. Previous studies demonstrated CXCR3 is expressed on CD4+ T cells in the spleen during malaria, but the phenotype was not defined. We identified the phenotype of CD4+ T cells that expressed CXCR3 in C57BL/6 (B6) mice during acute P. chabaudi AS infection by analyzing expression of the transcription factors T-bet and Foxp3. We also investigated if CXCR3 contributes to control of parasite replication and survival. The frequency and number of CD4+CXCR3+ T cells increased dramatically in the spleen of infected B6 mice coincident with increased CD4+IFN-+ T cells. CXCR3 was up-regulated on effector CD4+Foxp3- T cells as well as Foxp3+ Tregs. Consistent with our previous observations, CD4+T-bet+Foxp3- T cells increased in B6 mice during acute infection. T-bet+Foxp3+ Tregs also increased significantly and a high frequency of these cells expressed CXCR3 supporting the notion that these cells may be Th1-like Tregs. Despite this, the percentage of CD4+Foxp3+ Tregs from infected B6 mice that migrated in vitro to the CXCR3 ligands CXCL9 and CXCL10 was significantly less than naïve mice. To investigate the in vivo contribution of CXCR3 to control of acute blood-stage malaria, we compared the course and outcome of P. chabaudi AS infection in wild-type (WT) B6 and CXCR3-deficient mice. Parasitemia levels were significantly higher around the time of peak parasitemia in CXCR3-/- compared to WT mice but survival was similar suggesting a role for CXCR3 in controlling parasite replication during acute P. chabaudi AS infection. Together, our findings indicate Th1-like CD4+T-bet+Foxp3+ Tregs that express CXCR3 are induced during acute blood-stage malaria and suggest CXCR3 expression on CD4+ Th1 cells may contribute to their migration to the spleen.